Optimaliasi Partisipasi Masyarakat dalam Pengkemasan PUSAKA (Paket Eduwisata Historikal) Desa Bakas, Banjarangkan, Klungkung - Putra, Dewa (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
The development of tourism in Bakas Village focuses on strengthening locally based tourism activities through the PUSAKA Bakas (Historical Edu-Tourism Package); rural historical sightseeing and spiritual healing experience as the village’s. Despite its great potential, tourism activities in Bakas Village have not been optimally managed, and community participation as tourism service providers remains limited. This program aims to empower the community through capacity enhancement and active involvement in managing the village’s tourism potential. The method applied is Participatory Rural Appraisal (PRA) within the Entrepreneurship Capacity Building model through : planning, implementation, and evaluation. The activities include training on tourism package development, guiding skills enhancement, identification of the village’s physical and non-physical potentials, and the formulation of historical and spiritual tourism routes. This showed an increase in the understanding and skills of the Pokdarwis in developing educational tourism products based on local potentials. The program includes the identification of tourism potentials in Bakas Village; (a) development of tourism attractions; (b) identification of physical and non-physical potentials; (c) determination of points of interest; (d) optimization of community participation; and (e) interpretation in the PUSAKA into brochure. This program produces a sustainable model for developing historical edu-tourism based on community empowerment in Bakas Village.